Fikih Demonstrasi Perspektif Dewan Syariah Wahdah Islamiyah (Telaah Praktik Aksi Damai Wahdah Islamiyah di Kota Makassar) - Rosmita; Samin , Sabri; Abd. Wahid Haddade (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This study aims to describe the form of the Wahdah Islamiyah demonstration in the city of Makassar and to reveal how to formulate a fiqh demonstration so that it takes place safely and comfortably. Elaborating on the recommendations of the Syari'ah Council in dealing with anarchist protests. This research used field research (field research) with qualitative methods using a juridical approach (legislation), normative theological approach, and historical approach. The results of this study indicate; (a) The form of the Wahdah Islamiyah demonstration is based on the stipulation that the demonstration is the final step in solving the problem after the deliberation and dialogue stages have been carried out, the demands in the action are what is allowed in shari'ah, to be peaceful and to maintain Islamic ethics; (b) The manifestation of the implementation of the Wahdah Islamiyah demonstration in the 411 and 212 Peaceful Actions in Makassar City shows the realization of the fiqh of the demonstration established by the Syari'ah Wahdah Islamiyah Council so that it takes place safely, comfortably and productively; (c) Early education to all levels of society in the form of weekly intensive coaching (Tarbiyah) as the right solution recommended by the Syari'ah Wahdah Islamiyah Council in preventing anarchism demonstrations. The implication of this research is to provide understanding for public awareness of religion, nation, and state will form a pattern of problem-solving without violence but productively.